Analysis of risk factors of hepatocellular carcinoma and establishment of a clinical prognosis model - Ge, Xin-Yu; Sun, Ming-Chen; Wang, Tian-Yi; Wang, Xi-Min; Liu, Gang; Yang, Tao; Lu, Yi-Ming; Wang, Wei (Frontiers in Oncology, 2023)
Liver cancer is a common malignancy of the digestive system. Hepatocellular carcinoma (HCC) accounts for the most majority of these tumors and it has brought a heavy medical burden to underdeveloped countries and regions. Many factors affect the prognosis of HCC patients, however, there is no specific statistical model to predict the survival time of clinical patients.This study derived a risk factor signature of HCC and reliable clinical prediction model by statistically analyzing The Surveillance, Epidemiology, and End Results (SEER) database patient information using an open source package in the python environment.